2014
DOI: 10.1140/epjb/e2014-50615-1
|View full text |Cite
|
Sign up to set email alerts
|

Local boundary conditions for NMR-relaxation in digitized porous media

Abstract: We narrow the gap between simulations of nuclear magnetic resonance dynamics on digital domains (such as CT-images) and measurements in D-dimensional porous media. We point out with two basic domains, the ball and the cube in D dimensions, that due to a digital uncertainty in representing the real pore surfaces of dimension D − 1, there is a systematic error in simulated dynamics. We then reduce this error by introducing local Robin boundary conditions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…This study extends our previous work [15], that used local boundary conditions (LBC) to locally adapt the probability for surface relaxation, p S , when a NMR excitation encounters the pore surface in the porous medium. For simple domains we have shown that this method closely reproduces the solutions to the corresponding PDE model for which the surface relaxation is controlled by the surface relaxation parameter ρ via a Robin boundary condition [15]. It is clear that development towards more accurate numerical modeling benefit from predictions on well characterised samples, and the purpose of this article is to first carry out benchmarking simulations and then produce results for natural chalk samples.…”
Section: Introductionsupporting
confidence: 66%
See 4 more Smart Citations
“…This study extends our previous work [15], that used local boundary conditions (LBC) to locally adapt the probability for surface relaxation, p S , when a NMR excitation encounters the pore surface in the porous medium. For simple domains we have shown that this method closely reproduces the solutions to the corresponding PDE model for which the surface relaxation is controlled by the surface relaxation parameter ρ via a Robin boundary condition [15]. It is clear that development towards more accurate numerical modeling benefit from predictions on well characterised samples, and the purpose of this article is to first carry out benchmarking simulations and then produce results for natural chalk samples.…”
Section: Introductionsupporting
confidence: 66%
“…With the true (lowest) eigenvalues, λ j , for the ball and cube with physical parameters such as ρS/V = 3 and ρ = R 0 = D 0 = 1 reported in Table 1, we can compare the approximation in (15) 3) and (4)) is increasing by a factor 100 from (a) to (b), and from (b) to (c).…”
Section: Benchmarking Of the Numerical Methodsmentioning
confidence: 99%
See 3 more Smart Citations